2020
DOI: 10.3390/ijerph17228460
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sleep-Disordered Breathing in Children Referring for First Dental Examination. A Multicenter Cross-Sectional Study Using Pediatric Sleep Questionnaire

Abstract: Background: Sleep-related breathing disorders (SRDB) are a group of pathological conditions characterized by a dysfunction of the upper airways. The value of SRDB’s prevalence, in the pediatric population, ranges from 2 to 11% depending on the different methodologies used in measure and the difficulties in the diagnosis. The aim of this study was to assess the prevalence of SRDB using the Pediatric Sleep Questionnaire (PSQ). Methods: 668 patients were enrolled from the Department of Oral and Maxillo-Facial Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 39 publications
3
15
0
2
Order By: Relevance
“…The results of the present study showed that OSAS is a pathological condition with a significantly high prevalence in a selected population of children with neuromuscular, skeletal, genetic syndromes, and/or craniofacial abnormalities. The high prevalence of OSAS reported in this study (80.5%) is consistent with previously published studies for different populations and highlights the increased risk of OSAS among children with complex genetic disorders [ 17 , 21 , 23 , 26 ] compared with a much lower value of the prevalence of sleep-related breathing disorders (9.73%) in a general pediatric population [ 27 ]. Polysomnography played a key role in identifying OSAS in our pediatric population [ 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…The results of the present study showed that OSAS is a pathological condition with a significantly high prevalence in a selected population of children with neuromuscular, skeletal, genetic syndromes, and/or craniofacial abnormalities. The high prevalence of OSAS reported in this study (80.5%) is consistent with previously published studies for different populations and highlights the increased risk of OSAS among children with complex genetic disorders [ 17 , 21 , 23 , 26 ] compared with a much lower value of the prevalence of sleep-related breathing disorders (9.73%) in a general pediatric population [ 27 ]. Polysomnography played a key role in identifying OSAS in our pediatric population [ 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…58 In the United States, many general dentists reported that they screen for OSA by interview, identifying OSA-associated anatomic parameters, using a sleep questionnaire or ordering a home sleep apnea test. 59 Although the experiences of physicians outside the United States may not be comparable to the experiences of There is a dearth of sleep physicians in the United States, according to a recent report from the 2018 American Academy of Sleep Medicine President, Dr. Ilene Rosen, largely due to the attrition rate of retiring sleep physicians from the workforce, which far exceeds the slow uptake of physicians seeking to replace them. 60 This speaks to an increasing gap in addressing the public health problem of OSA, especially with already low rates of recognition of sleep disorders in primary care.…”
Section: Discussionmentioning
confidence: 99%
“…OSA adalah SRBD yang paling sering terjadi pada anak anak maupun dewasa, berupa berhentinya aliran udara pada hidung dan mulut yang bertahan selama minimal 10 detik saat pasien dalam keadaan tidur (1). OSA pada usia anakanak mulai mendapat perhatian lebih pada tahun berikutnya (1976) dikarenakan cukup signifikannya prevalensi gangguan sampai mencapai 4 % dan makin meningkat pada beberapa tahun terakhir (3)(4)(5)(6). Kondisi anak dengan OSA apabila tidak terdeteksi dan tidak dilakukan perawatan lebih lanjut akan menyebabkan keluhan rasa mengantuk berlebihan di siang hari, masalah perilaku, ketidakmampuan belajar, kelainan jantung dan kegagalan dalam pertumbuhan yang akan berpengaruh pada saat anak tersebut dewasa (7)(8)(9).…”
Section: Latar Belakangunclassified